Rape on the contemporary stage - Fitzpatrick, Lisa (Palgrave Macmillan, 2018)
"This volume investigates the representation of rape in British and Irish theatre since the second wave of the Women's Movement. Mainly focusing on the period from the 1990s to the present, it identifies key feminist debates on rape and gender, and introduces a set of ideas about the function of rape as a form of embodied, gendered violence to the analysis of dramaturgical and performance strategies used in a range of important and/or controversial works"--